Commodification of higher education? : an analysis of Education and Training Sector Improvement Programme (ETSIP) phase 1 (2006 to 2011) document of Namibia's 2005 to 2020 education programme - Mbhele, Nomonde (2017)
The conceptualization of education is an essential term which generally tends to be understood in different ways, this is especially in terms of how it is supposed to function in the society. For Namibia, the notion of education in Namibia is emphasised as an important sector to enable the country to achieve developmental goals. This is partly because of the education perspective(s) that has shaped how the concept of education is theoretically and practically understood from legislative framework to policy discourse.